Drying Precess-A Factor That Ensures Long-Term Storage Of Agricultural Raw Materials - Akabirov Laziz Isamidinov; Gafurov Karim Hakimovich; Majidov Kakhramon Halimovich (The American Journal of Engineering and Technology, 2020)
It is shown that the main factors providing the processes of drying agricultural raw materials are thermophysical properties and dimensions, the shape and condition of the outer surface, the interval of changes in the moisture content of the material during the drying process, etc. The internal structure of the material has the strongest effect on the drying process. For dispersed materials with particles with a diameter of more than 2 mm and a critical pore radius of less than 2 nm, the duration of convective drying is more than 1 h, while for dispersed materials with a critical pore radius of more than 100 nm (all other things being equal) it is within 0.5 - 3 p.